Affirmative Action and Federal Character Principle in the U.S. and Nigeria: Implications for Nation Building - Osemeka, Irene N. (Àgídìgbo: ABUAD Journal of the Humanities, 2016)
Affirmative Action (AA) and Federal Character Principle (FCP) are policies adopted by the U.S. and Nigerian governments respectively to achieve equitable representation of various segments of their population in public institutions. The approaches complement other policies that aim to foster peaceful coexistence among diverse ethnic and racial groups in both countries. Critics have however argued that the implementation of the policies is only reinventing discrimination through preferential treatment of hitherto disadvantaged groups. The article’s position is that policies such as AA and FCP are appropriate to redress inequities so as to close the gap in access to opportunities by different groups and therefore enhance the process of nation building in both countries. In line with this submission, the paper recommends continuous review of AAlFCP to reflect contemporary challenges in ethnic/racial relations in both countries. For instance the mass incarceration of African Americans indicates that AA needs to be expanded beyond the sphere of employment and education to include other aspects of public life including the justice system. In the case of Nigeria, there is need to strengthen the rules guiding the Federal Character Commission (FCC) and its powers to prosecute offenders to ensure that the implementation of FCP remains fair and transparent and does not become an additional avenue for the marginalization of the masses by the ruling elite.